Prevalence of anaemia and the associated factors among hospitalised people living with HIV receiving antiretroviral therapy in Southwest China: a cross-sectional study - Jie Yuan; Hai Long; Min Liu; Juan He; Jue Liu; Yu Wu; Wenzhan Jing; Min Du; Manna Zhang; Yaping Wang; Su Song; Siqi Liu; et al. (BMJ Open)
Objectives To estimate anaemia prevalence and the associated factors among hospitalised people living with HIV (PLHIV) receiving antiretroviral therapy (ART).Design A cross-sectional study.Setting PLHIV receiving ART and hospitalised in a specialised hospital for infectious disease in Guizhou Province, Southwest China, between 1 January 2018 and 31 March 2021.Participants A total of 6959 hospitalised PLHIV aged ≥18 years and receiving ART were included in this study.Primary and secondary outcome measures Anaemia was diagnosed as a haemoglobin concentration <120 g/L for non-pregnant females and <130 g/L for males. Mild, moderate and severe anaemia were diagnosed as below the gender‐specific lower limit of normal but ≥110 g/L, 80–110 g/L and <80 g/L, respectively.Results The prevalence of anaemia was 27.5%, and that of mild, moderate and severe anaemia was 9.2%, 12.2% and 6.1%, respectively. Results from multivariate logistic regression showed that females had increased odds of anaemia (adjusted OR (aOR)=1.60, 95% CI: 1.42 to 1.81) compared with males. Widowed or divorced inpatients (anaemia: aOR=1.26, 95% CI: 1.08 to 1.47; severe anaemia: aOR=1.52, 95% CI: 1.16 to 1.97) and thrombocytopenia inpatients (anaemia: aOR=4.25, 95% CI: 3.54 to 5.10; severe anaemia: aOR=4.16, 95% CI: 3.24 to 5.35) had increased odds of anaemia and severe anaemia compared with their counterparts. Hepatitis C was associated with increased odds of severe anaemia (aOR=1.80, 95% CI: 1.11 to 2.92).Conclusions Anaemia was prevalent among hospitalised PLHIV. Female sex, those widowed or divorced, and thrombocytopenia were associated with increased odds of anaemia, and those widowed or divorced, thrombocytopenia and hepatitis C were associated with increased odds of severe anaemia. Determination of anaemia predictors, early detection and timely management of anaemia are crucial to prevent anaemia progression.